2004
DOI: 10.1097/01.prs.0000122207.28773.56
|View full text |Cite
|
Sign up to set email alerts
|

The Patient and Observer Scar Assessment Scale: A Reliable and Feasible Tool for Scar Evaluation

Abstract: At present, various scar assessment scales are available, but not one has been shown to be reliable, consistent, feasible, and valid at the same time. Furthermore, the existing scar assessment scales appear to attach little weight to the opinion of the patient. The newly developed Patient and Observer Scar Assessment Scale consists of two numeric scales: the Patient Scar Assessment Scale (patient scale) and the Observer Scar Assessment Scale (observer scale). The patient and observer scales have to be complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
739
3
19

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,043 publications
(807 citation statements)
references
References 10 publications
6
739
3
19
Order By: Relevance
“…Scar assessment scale wasPatient and Observer Scar Assessment Scale (POSAS).The observer scale of the POSAS consists of six items All items are scored on a scale ranging from 1 ('like normal skin') to 10 ('worst scar imaginable'). Both total and overall opinion was studied.Draaijers LJ, Tempelman FR, BotmanYA (18) showed that POSASScale offers a suitable, reliable, and complete scar evaluation tool. Both Total and Overall POSAS score was significantly less (p=0.002 & p=0.003 respectively) in subcuticular group.Overall best cosmetic appearance of skin was with subcuticular followed by simple interrupted and comparatively worst with stapler.…”
Section: Cosmetic Acceptability Of Scarmentioning
confidence: 99%
“…Scar assessment scale wasPatient and Observer Scar Assessment Scale (POSAS).The observer scale of the POSAS consists of six items All items are scored on a scale ranging from 1 ('like normal skin') to 10 ('worst scar imaginable'). Both total and overall opinion was studied.Draaijers LJ, Tempelman FR, BotmanYA (18) showed that POSASScale offers a suitable, reliable, and complete scar evaluation tool. Both Total and Overall POSAS score was significantly less (p=0.002 & p=0.003 respectively) in subcuticular group.Overall best cosmetic appearance of skin was with subcuticular followed by simple interrupted and comparatively worst with stapler.…”
Section: Cosmetic Acceptability Of Scarmentioning
confidence: 99%
“…Nevertheless, many studies have reported increased patient gratification with the overall appearance of their scars when thoracotomies were used to close ASDs, although these findings have not been supported by any patient surveys or interviews. [25] Draaijers et al [26] reported that the POSAS is a more suitable, reliable, and complete scar evaluation tool than the VSS, but we found that the VSS and POSAS yielded similar wound characteristics and produced comparable results. However, the incidence of unpleasant hypertrophic scar formation in our study was higher in the patients with MS.…”
Section: Discussionmentioning
confidence: 48%
“…Para a analgesia pós-operatória, utilizou-se Dipirona 8 mg por kg de peso, endovenosa (EV), de 6 em 6 h e Tenoxican 0,3 mg por kg de peso, EV, de 12 em 12 h e, se necessário, Quando as pacientes retornaram para a revisão de 12 meses de pós-operatório foi aplicada a Escala Paciente e Observador de Avaliação da Cicatriz (EPOAC) 7 . Esta escala consiste em duas escalas numéricas: a preenchida pelo paciente, que contém seis itens (dor, prurido, coloração, endurecimento, espessura e irregularidade) e a do observador, que contém cinco itens (vascularização, espessura, relevo, maleabilidade e pigmentação).…”
Section: Métodounclassified
“…A contagem 10 reflete a pior cicatriz ou sensação imaginável, já a 1 reflete uma pele normal. As contagens totais mais baixas, 6 e 5, respectivamente, refletem a pele normal, enquanto que contagens totais mais altas, 60 e 50, respectivamente, refletem a pior cicatriz imaginável 7,8 . O cálculo do tamanho da amostra foi baseado em α = 0,05 com um poder de estimativa de 0,80 utilizando o programa de computador PS: Power and Sample Size (Vanderbilt University Medical Center, Nashville, EUA).…”
Section: Métodounclassified